Humanin exerts cardioprotection against cardiac ischemia/reperfusion injury through attenuation of mitochondrial dysfunction - Thummasorn S. (2017)
© 2016 John Wiley & Sons Ltd Aim: Myocardial reperfusion via the re-canalization of occluded coronary arteries is gold standard for the treatment of acute myocardial infarction. However, reperfusion itself can cause myocardial damage due to increased reactive oxygen species (ROS) production, a process known as ischemia/reperfusion (I/R) injury. Cardiac mitochondria are the major organelle of ROS production in the heart. Cardiac mitochondrial dysfunction caused by an increased ROS production can increase cardiac arrhythmia incidence, myocardial infarct size, and cardiac dysfunction. Thus, preservation of cardiac mitochondrial function is a promising pharmacological approach to reduce cardiac I/R injury. Humanin (HN), a newly discovered 24-amino acid polypeptide, has been shown to exert antioxidative stress and antiapoptotic effects. Although the cardioprotective effects of HN against I/R injury has been reported, the effect of HN on cardiac mitochondrial function has not yet been investigated. Thus, we tested the hypothesis that HN exerts its cardioprotective effects against I/R injury through the attenuation of cardiac mitochondrial dysfunction. Methods: I/R protocol was carried out using a 30-minutes occlusion of a left anterior descending coronary artery followed by a 120-minutes of reperfusion. The plasma HN level, infarct size, arrhythmia incidence, left ventricular function, and cardiac mitochondrial function were determined. Results: Endogenous HN level before I/R injury showed no difference between groups, but was markedly decreased after I/R injury. HN analogue pretreatment decreased arrhythmia incidence and infarct size, improved cardiac mitochondrial function, and attenuated cardiac dysfunction. Conclusions: Humanin analogue pretreatment exerted cardioprotective effects against I/R injury through the attenuation of cardiac mitochondrial dysfunction.